Specific antitumor activity of anti-CA125 CAR-T lymphocytes against CA125-positive and CA125-negative cells - T. M. Kulinich; Ya. Yu. Kiseleva; A. M. Shishkin; E. A. Kudinova; O. B. Knyazeva; R. Ranjit; V. K. Bozhenko; V. A. Solodky (Сеченовский вестник, 2024)
Aim. To evaluate the antitumor efficacy of our developed drug based on cytotoxic T lymphocytes genetically modified with a chimeric antigen receptor (CAR) specific to the CA125 antigen in relation to both CA125-positive and CA125negative cell cultures.Materials and methods. We performed an in vitro study on CA125-positive human ovarian cancer cells (OVCAR-3, OVKATE) and CA125 negative cells (breast cancer MCF 7, embryonic kidney HEK293). Cytotoxic effects on tumor cells were evaluated after 0, 4, 8 and 24 hours using the 3’-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) and Lactate Dehydrogenase (LDH) tests. We also studied the changes in the number of cells “in real time” when exposed to transfected lymphocytes using the RTCA iCELLIgence device (ACEA Biosciences, USA). Lymphokineactivated killer (LAK) cells were used as a specificity control.Results. The study demonstrated that anti-CA125 CAR-T lymphocytes exhibited a pronounced cytotoxic effect on OVCAR-3 and OVKATE cell cultures, exceeding the effect of LAK by 1.3 times. The cell population in the experimental samples decreased by 70 ± 4%, which exceeded the LAK effect by 9 ±  8.2%. With regard to the MCF-7 cell line, the cytotoxic effect of anti-CA125 CAR-T lymphocytes was minimal as evidenced by a 25.8% decrease in the relative number of live cells in comparison to the LAK cytotoxicity of 68%. Real-time monitoring of cell proliferation and viability proved a high specific cytotoxic effect of anti-CA125 CAR-T lymphocytes against tumor cultures expressing CA-125, while inferior to LAK in cultures not expressing CA125 (MCF-7, HEK293).Conclusions. The use of anti-CA125 CAR-T lymphocytes against CA125-positive tumor cell lines OVCAR-3 and OVKATE demonstrated a pronounced specific cytotoxic effect exceeding the cytotoxic effect of LAK, which was not achieved against CA125-negative MCF-7 and HEK293 cells.